Digital game addiction - Batdi, Veli; Doğan, Yunus; Tüter, Mekselna (Nova Science Publishers Inc., 2025)
This article explores the evolution of games from traditional outdoor activities to digital platforms, highlighting the profound impact of technological advancements on gaming and the emergence of digital game addiction. Initially, games were predominantly physical, played with natural materials in outdoor settings, but over time, urbanization, technological development, and cultural shifts have driven a transition towards digital gaming. The digitalization of games has led to both positive and negative consequences. On the one hand, digital games enhance communication skills, problem-solving abilities, creativity, and hand-eye coordination. On the other hand, they have been linked to social isolation, health problems, declining academic performance, and increased aggression. As digital games have become more integrated into daily life, concerns about digital game addiction have grown. Digital game addiction is characterized by excessive, uncontrolled gaming that disrupts daily life, causes emotional and social issues, and is challenging to reduce. This article examines the criteria for diagnosing digital game addiction, including preoccupation with gaming, withdrawal symptoms, and the neglect of other activities. The paper also discusses various types of digital games, such as strategy, puzzle, adventure, simulation, and sports games, emphasizing their different purposes and appeal. To address digital game addiction, the article offers recommendations for families, governments, and game developers. These include setting time limits, encouraging alternative activities, monitoring game content, and implementing age restrictions. Additionally, the article highlights the role of education and public awareness in preventing addiction. Finally, the paper examines digital game addiction across different educational levels, noting the importance of parental involvement and early intervention in mitigating the risks associated with digital gaming. © 2025 Nova Science Publishers, Inc. All rights reserved.
Keywords: Criteria for game addiction; Digital games; Game addiction; Negative aspects of digital games